Pharmacoeconomics and the Patients’ Compliance as an Essential part of Successful therapy of iron Deficiency Anemia. - Khodjieva Gulirano Sayfullaevna (Universitas Muhammadiyah Sidoarjo, 2022)
This article is devoted to pharmacoeconomics and patients’ compliance to the therapy of iron deficiency anemia. These directions are relatively young in science and their importance often remains underestimated by most specialists. Pharmacoeconomics’ main goal is to determine the most optimal medicine for treating the disease’s cost-effectiveness ratio. Therefore, this review presents the main facts that determine the therapeutic efficacy of specific iron preparations and their clinical and economic analysis results. It also provides the statistical and theoretical substantiation of the significance of research and control of patients’ compliance in the treatment of iron deficiency anemia.